Using the new Scottish Longitudinal Outcomes database (LEO) to understand transitions from university to practice amongst nursing students - Pearsons, Alice; Mitchell, Eleanor; Shields, Euan; Atherton, Iain (International Journal of Population Data Science, 2025)
Objectives Nursing is facing substantial workforce challenges. Applications to study nursing have declined by 25% in Scotland, while 900 vacancies remain unfilled. The NHS Long Term Workforce Plan aims to grow the UK nursing workforce from 350,000 to 550,000 nurses by 2036/37. However, little is known about nursing students’ progression into practice. Methods This study proposes using the Scottish Longitudinal Outcomes database (LEO) to establish the early career trajectories of nursing students graduating from Scottish Universities. This new data linkage brings together data from Scottish universities (Higher Education Statistics Agency) from academic year 2003/04 to 2018/19 and employment data drawn from HMRC. Taken together, this will provide analysis of the early career trajectories of newly qualified nurses in Scotland. Findings will represent the first time that the Scottish LEO has been used for projects outside the Scottish Government. Results Descriptive statistics will ascertain the proportions of nursing students who entered into a career in healthcare using SIC codes. The extent to which first year graduates do not achieve a clinical post will be reported, other occupations entered, and the extent to which no employment is achieved. For those who do not achieve employment straightaway, or who go into positions outside of health, the length of time to first nursing position will be assessed. Results of survival models will be reported to assess how long it takes to achieve a clinical position from graduation. Models will explore the extent to which entry to clinical roles is influenced by socio-demographic characteristics and the extent to which the situation has changed over time. Conclusion To our knowledge, this study will provide the first insights into the implications of early career nurses securing employment within nursing. Given declines in recent programme entries and costs of training, these findings will hold considerable policy potential.